Genome-Wide Association Study Reveals a Genetic Mechanism of Salt Tolerance Germinability in Rice (Oryza sativa L.) - Li, Caijing; Lu, Changsheng; Zou, Baoli; Yang, Mengmeng; Wu, Guangliang; Wang, Peng; Cheng, Qin; Wang, Yanning; Zhong, Qi; Huang, Shiying; Huang, Tao; He, Haohua; et al. (Frontiers in Plant Science, 2022)
Salt stress is one of the factors that limit rice production, and an important task for researchers is to cultivate rice with strong salt tolerance. In this study, 211 rice accessions were used to determine salt tolerance germinability (STG) indices and conduct a genome-wide association study (GWAS) using 36,727 SNPs. The relative germination energy (RGE), relative germination index (RGI), relative vigour index (RVI), relative mean germination time (RMGT), relative shoot length (RSL) and relative root length (RRL) were used to determine the STG indices in rice. A total of 43 QTLs, including fifteen for the RGE, six for the RGI, seven for the RVI, three for the RMGT, one for the RSL and eleven for the RRL, were identified on 9 chromosome regions under 60 mM NaCl and 100 mM NaCl conditions. For these STG-related QTLs, 18 QTLs were colocalized with previous studies, and some characterized salt-tolerance genes, such as OsCOIN, OsHsp17.0, and OsDREB2A, are located in these QTL candidates. Among the 25 novel QTLs, qRGE60-1-2 colocalized with qRGI60-1-1 on chromosome 1, and qRGE60-3-1 and qRVI60-3-1 colocalized on chromosome 3. According to the RNA-seq database, 16 genes, including nine for qRGE60-1-2 (qRGI60-1-1) and seven for qRGE60-3-1 (qRVI60-3-1), were found to show significant differences in their expression levels between the control and salt treatments. Furthermore, the expression patterns of these differentially expressed genes were analysed, and nine genes (five for qRGE60-1-2 and four for qRGE60-3-1) were highly expressed in embryos at the germination stage. Haplotype analysis of these nine genes showed that the rice varieties with elite haplotypes in the LOC_Os03g13560, LOC_Os03g13840 and LOC_Os03g14180 genes had high STG. GWAS validated the known genes underlying salt tolerance and identified novel loci that could enrich the current gene pool related to salt tolerance. The resources with high STG and significant loci identified in this study are potentially useful in breeding for salt tolerance.